Profile of a Digital Era Humanist PAI Teacher (Humanist Studies in Gender Equality) - Salsabilla Utami; Indah Sarimulia; Putri Padilla Panjaitan; Roby Ardhana (Journal of Contemporary Gender and Child Studies, 2023)
This paper aims to describe how the attitude of PAI teachers in teaching in the digital era which along with the development of sophisticated technology, many changes in attitudes and behavior of teachers in teaching, especially the lack of understanding in using technology will actually make it easier for teachers in the learning process of students who will be more efficient, but there is an attitude generated by the teacher in trying to integrate knowledge with other sciences, so that there will be an impact where students are less concerned with the teacher and the lessons being delivered and lose the will to learn a science. The method used in this paper is literature study by analyzing and reviewing various literature such as books and related journal documents. The results of this paper expect an PAI teacher to become an educator who carries out his duties properly and plays a full role in implementing humanist learning in this digital era.